ENGAGEMENT COMMUNICATION PROCESSES OF PENTAHELIX MODEL STAKEHOLDER WITHIN MAJESTIC BANYUWANGI TOURISM PROJECT MANAGEMENT - Althofi Rozaan; Bambang Dwi Prasetyo; Ananda Sabil Hussein (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This research examines the engagement communication strategies of various Pentahelix model actors in the management of tourism destinations in the Majestic Banyuwangi program. A qualitative research method was employed, with interviews serving as the data collection technique. The study indicates that the five Pentahelix actors, consisting of the government, businesses, academics, communities, and the media, play crucial roles in building engagement communication strategies. The government regulates and facilitates, businesses act as adept negotiators, academics shape understanding of issues, communities serve as decision-making centers, and the media act as information disseminators. Engagement communication strategies based on the Pentahelix model can enhance community participation and strengthen inter-actor relationships. Cross-sector collaboration and community participation bolster the development of cultural tourism. With effective promotion and holistic communication strategies, Majestic Banyuwangi has the potential to become a globally competitive tourist destination, particularly in cultural tourism.